Diversification Strategy : A Study of Malaysian Conglomerates - Chen, Lin Yow (2014)
Diversification strategy involves decisions about the products that a firm should make and the markets that it competes in. It is a matter that is of great importance to corporate level managers. This report examines the conglomerate approach to diversification, essentially a strategy of broad expansion through the addition of new businesses that are unrelated to existing ones. There are three objectives to this study. The first was to investigate the relationship between the degree of diversification and financial performance. Using an initial sample that consisted of the 30 largest publicly listed companies in Malaysia, this investigation was, therefore, carried out in the context of an emerging economy, where it has been suggested that conglomerates perform well. However, results show that the related model of diversification produces the best overall performance. Subsequently, in the second objective, case studies were conducted on three large Malaysian based conglomerates inorder to determine if and how synergies can exist in Spite of the unrelated nature of their various businesses. Here, 17 synergies were found, and this report identifies the synergies that are considered to be the most useful. Finally, in the third objective, recommendations were made for the three case study conglomerates in terms of the style that should be employed by the corporate parent in managing their businesses.